2017
DOI: 10.1038/s41598-017-17792-2
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Bisvinyl Sulfonemethyl-crosslinked Gelatin Conduit Promotes Regeneration after Peripheral Nerve Injury in Adult Rats

Abstract: In our previous study, we found that gelatin-based materials exhibit good conductivity and are non-cytotoxic. In this study, gelatin was cross-linked with bisvinyl sulfonemethyl (BVSM) to fabricate a biodegradable conduit for peripheral nerve repair. First, BVSM on the prepared conduit was characterized to determine its mechanical properties and contact angle. The maximum tensile strength and water contact angle of the gelatin-BVSM conduits were 23 ± 4.8 MPa and 74.7 ± 9°, which provided sufficient mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 50 publications
1
18
0
1
Order By: Relevance
“…As a natural protein biopolymer, gelatin possesses some beneficial properties such as availability, cost‐effectiveness, biocompatibility, biodegradability, having no toxic by‐products after enzymatic degradation, stimulation of cellular adhesion, and suitability for drug delivery (Elzoghby, ) and releasing growth factors (Chang et al, ). Previous studies have also shown that the use of gelatin conduits produced by various methods stimulates damaged nerve growth in a rat model (Ko et al, ; Tao et al, ). Moreover, it has been exhibited that NGF immobilized on SC‐loaded gelatin conduits can improve nerve regeneration in a 10‐mm rat sciatic nerve gap model (Chen et al, ).…”
Section: Materials For Fabricating Nerve Conduitsmentioning
confidence: 93%
See 1 more Smart Citation
“…As a natural protein biopolymer, gelatin possesses some beneficial properties such as availability, cost‐effectiveness, biocompatibility, biodegradability, having no toxic by‐products after enzymatic degradation, stimulation of cellular adhesion, and suitability for drug delivery (Elzoghby, ) and releasing growth factors (Chang et al, ). Previous studies have also shown that the use of gelatin conduits produced by various methods stimulates damaged nerve growth in a rat model (Ko et al, ; Tao et al, ). Moreover, it has been exhibited that NGF immobilized on SC‐loaded gelatin conduits can improve nerve regeneration in a 10‐mm rat sciatic nerve gap model (Chen et al, ).…”
Section: Materials For Fabricating Nerve Conduitsmentioning
confidence: 93%
“…The time required for nerve regeneration is at least 2 months (Ko et al, ); however, a study reported a time period of 18 months for nerve regeneration, highlighting that more time is required for the sensory and motor function recovery (Das et al, ).…”
Section: The Necessary Work Before During and After The Conduit Impmentioning
confidence: 99%
“…Variables include the types of electrical stimulation (constant/pulse of direct/alternating current), stimulation parameters (frequency and intensity), and the sites of placement of electrodes have also been studied [23]. In the research of nerve conduits, numerous materials have been developed to repair peripheral nerve injury, such as silicone rubber [23,40], gelatin [41], polyglycolic acid [42], polyurethane [41], poly(l-lactide-co-caprolactone) [43], and so on. These nerve conduits are usually designed as a tubular structure, which could provide mechanical orientation and confinement to aid growing nerve fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Nerve regeneration at 8 weeks in a 10 mm rat sciatic nerve defect repaired through this conduit was similar to that obtained using a silicone guide previously tested. Gelatin cross-linking with bisvinylsulfonemethyl reduces gelatin swelling and improves its mechanical properties; moreover, unlike other gelatin conduits, this nerve guide is transparent (Ko et al, 2017).…”
Section: Wang Et Al 2018bmentioning
confidence: 99%